Girirāj Kiśor's Yātrāeṁ : A Hindi Novel Analysed - Damsteegt, Theo, (Asian Studies - Book Archive pre-2000., 1997)
This book is one of the first to present a detailed analytic study of a novel written in Hindi. Its in-depth analysis of the complete text of Kiśor's Yātrāeṁ (1971) is based on narratology and a study of connotations and cultural background. The extensive introduction - especially into narratology - and the inclusion of the integral Hindi text of the novel together with a Hindi-English glossary and word index allow the reader, not only to follow the analysis in all its detail but also to use the book as a practical example of how modern Hindi prose literature may be analysed. Yātrāeṁ is no exception to a trend in modern Hindi novel writing to focus on individual experience and on love and sexual relationships, but its concentration on the way in which a man experiences his wedding night and honeymoon lends it a special character. It is the groom himself who narrates and interprets the couple's lack of success in fully consummating the marriage. Since he is personally involved in the events, his account is highly subjective, and it is left to the reader to find out what could be the real cause of the events. Reviews of Yātrāeṁ propose diverse interpretations, which are all based on intuitive readings. This book shows how a systematic analysis of the text leads to a different interpretation. The analysis highlights how conscious and unconscious ideas about gender roles, activeness and passiveness, dominance, passion, control, and balance determine the man's behaviour towards the woman. As observed in the Introduction, the philosophy of disinterested action as taught by the Bhagavadgītā is found to be relevant even today.